Under suspicion : a phenomenology of media - Grojs, Boris (Columbia themes in philosophy, social criticism, and the arts, 2012)
The submedial subject and the flux of signs -- The truth of the medial and the state of exception -- The media-ontological suspicion and philosophical skepticism -- The phenomenology of medial sincerity -- The gaze of the other -- The medium becomes the message -- The case of exception and the truth of the medial -- Marcel Mauss: symbolic exchange or civilization under water -- Claude Lévi-Strauss: mana or the floating signifier -- Georges Bataille: the potlatch with the sun -- Jacques Derrida: the lack of time and its ghosts -- Jean-François Lyotard: the roller-coaster of the sublime -- The time of signs -- Suspicion is the medium